Evaluation of Journal Management Through Dialogic Communication: A Content Analysis of Agrivita International Journal of Agricultural Science Website - Wahyuni, Silvia Santi; Kriyantono, Rachmat; Safitri, Reza; Kuswanto, Kuswanto (AGRIVITA Journal of Agricultural Science, 2025)
The paper was intended to measure the website of Agrivita Journalin the implementation of dialogic communication features. Thesecommunicative features indicate the management capability in thedigital-based scientific journal process. The content analysis wasemployed, utilizing 31 dialogic communication features that five codersevaluated as the assessment instrument. The Intraclass CorrelationCoefficient (ICC) approach was used to measure inter-rater reliability,and a composite index was used to assess the implementation strengthof each feature. The results showed that the ICC calculation based on thetwo-way random effects model and absolute agreement was consideredreliable. ICC values of features such as the layout of the Agrivitawebsite, the publisher profile page, and visitor statistics were scored1.00, indicating that the respective features perform an exceptional andconsistent execution in facilitating effective bidirectional communication.Meanwhile, minimal ratings resulted from features like the FAQ page,referring to the lack of information transparency and participation fromwebsite users. This study also indicated that improving interactive andinformative elements on the website is substantial to induce higherparticipation from the scientific users. Moreover, the study also pointedout that the evaluation conducted by journal management shouldinclude principles of dialogic communication as a strategic referenceto enhance governance quality and achieve international indexing.